The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7554/elife.76411
|View full text |Cite
|
Sign up to set email alerts
|

Spatially bivariate EEG-neurofeedback can manipulate interhemispheric inhibition

Abstract: Human behavior requires interregional crosstalk to employ the sensorimotor processes in the brain. Although external neuromodulation techniques have been used to manipulate interhemispheric sensorimotor activity, a central controversy concerns whether this activity can be volitionally controlled. Experimental tools lack the power to up- or down-regulate the state of the targeted hemisphere over a large dynamic range and, therefore, cannot evaluate the possible volitional control of the activity. We addressed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 115 publications
(177 reference statements)
0
7
0
Order By: Relevance
“…Transcranial magnetic stimulation (TMS) Problems with the motor cortex have been extensively studied by using TMS, with 18 articles dedicated to the issue: those by Ros et al ( 2010 ), Niazi et al ( 2012 ), Sitaram et al ( 2012 ), Mokienko et al ( 2013 ), Takemi et al ( 2013 , 2018 ), Hänselmann et al ( 2015 ), Kaplan et al ( 2016 ), Royter and Gharabaghi ( 2016 ), Schildt et al ( 2016 ), Hasegawa et al ( 2017 ), Mashat et al ( 2017 ), Daly et al ( 2018 ), Jochumsen et al ( 2018 ), Syrov et al ( 2020 ), Ding et al ( 2021 ), Grigorev et al ( 2021 ), and Mihelj et al ( 2021 ) for neugodegenerative disease. The second most commonly studied disease by using TMS was stroke, with five articles devoted to it: those by Gharabaghi et al ( 2014 ), Syrov et al ( 2019 ), Cantillo-Negrete et al ( 2021 ), Hayashi et al ( 2022 ), and Liang et al ( 2020 ). Four articles examine the sensorimotor cortex: those by Pichiorri et al ( 2011 ), Niazi et al ( 2014 ), Kraus et al ( 2016 ), and Naros et al ( 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS) Problems with the motor cortex have been extensively studied by using TMS, with 18 articles dedicated to the issue: those by Ros et al ( 2010 ), Niazi et al ( 2012 ), Sitaram et al ( 2012 ), Mokienko et al ( 2013 ), Takemi et al ( 2013 , 2018 ), Hänselmann et al ( 2015 ), Kaplan et al ( 2016 ), Royter and Gharabaghi ( 2016 ), Schildt et al ( 2016 ), Hasegawa et al ( 2017 ), Mashat et al ( 2017 ), Daly et al ( 2018 ), Jochumsen et al ( 2018 ), Syrov et al ( 2020 ), Ding et al ( 2021 ), Grigorev et al ( 2021 ), and Mihelj et al ( 2021 ) for neugodegenerative disease. The second most commonly studied disease by using TMS was stroke, with five articles devoted to it: those by Gharabaghi et al ( 2014 ), Syrov et al ( 2019 ), Cantillo-Negrete et al ( 2021 ), Hayashi et al ( 2022 ), and Liang et al ( 2020 ). Four articles examine the sensorimotor cortex: those by Pichiorri et al ( 2011 ), Niazi et al ( 2014 ), Kraus et al ( 2016 ), and Naros et al ( 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we explore the interhemispheric functional connectivity of a region that responds to our stimuli, assessing its potential as a target for neuromodulation at different TRs. This has been successfully applied before in other neurofeedback paradigms (Pereira et al, 2019;Wang et al, 2020;Hayashi et al, 2022). Speci cally, we simulated the feedback of the perceptual switches based on the hMT + interhemispheric correlation value.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that functional connectivity at rest implies the structured pattern of brain networks associated with task-induced functional connectivity [39]. Therefore, we assessed functional connectivity during the 'Rest' epoch by computing the network intensity [11,40] based on the corrected imaginary part of coherence (ciCOH) measure [11,[40][41][42]. Specifically, ciCOH was initially estimated from preprocessed EEG data that were segmented every 1 s in the 'Rest' epoch with 50% overlap and multiplied by the Hanning window [11,41].…”
Section: Resting-state Functional Connectivitymentioning
confidence: 99%
“…Specifically, ciCOH was initially estimated from preprocessed EEG data that were segmented every 1 s in the 'Rest' epoch with 50% overlap and multiplied by the Hanning window [11,41]. Subsequently, the ciCOH value was computed from the complex coherency function of the segmented data [11,[40][41][42]:…”
Section: Resting-state Functional Connectivitymentioning
confidence: 99%
See 1 more Smart Citation